Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4172/2329-9096.1000210
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supervised Exercise Training on Symptoms of Chemotherapy-Induced Peripheral Neuropathy

Abstract: Chemotherapy-Induced Peripheral Neuropathy is a common, dose-limiting effect of chemotherapy treatment. Pharmacological therapies are largely uneffective, making the investigation of other interventions warranted. Homebased exercise programs have produced promising improvements in quality of life and pain symptoms, yet compliance to programs is low. Thus, the purpose of this investigation was to examine the outcomes of a structured, supervised exercise program in reducing symptoms of CIPN and improving physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…Physical activity and lifestyle interventions with cancer survivors have been shown to be efficacious for both weight [31, 32] and pain management [33], as well as improving HRQoL [3436]. Evidence is emerging that physical activity is effective in ameliorating CIPN symptoms in particular [37, 38]. Interventions using components of cognitive behavioral therapies have also been successful in targeting a range of issues pertinent to cancer survivorship [39, 40], including weight management [40], pain [41, 42], and HRQoL [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity and lifestyle interventions with cancer survivors have been shown to be efficacious for both weight [31, 32] and pain management [33], as well as improving HRQoL [3436]. Evidence is emerging that physical activity is effective in ameliorating CIPN symptoms in particular [37, 38]. Interventions using components of cognitive behavioral therapies have also been successful in targeting a range of issues pertinent to cancer survivorship [39, 40], including weight management [40], pain [41, 42], and HRQoL [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Also clinical trial conducted on patients investigated the role of exercise in the management of peripheral neuropathy [ 71 ]. Two studies that tested a structured 10-12 weeks exercise programs (one supervised, the other home-based) found that exercise training reduces CIPN symptoms, such as unpleasant skin sensations, sensitivity related to neuropathic pain and the experience of coming on suddenly in bursts for no apparent reason [ 87 , 88 ].…”
Section: Physical Aspectsmentioning
confidence: 99%
“…A follow-up investigation examined the effect of 12 weeks of supervised exercise training on symptoms of CIPN and found that exercise training positively impacted neurological function. Specifically, unpleasant skin sensations and sensitivity related to neuropathic pain were attenuated following chronic exercise training [57].…”
Section: Exercise Rehabilitationmentioning
confidence: 97%